Responsitas Pemerintahan Daerah Terhadap Krisis Ekonomi (Studi Kasus Program Perluasan Lapangan Kerja dan Pendayagunaan Tenaga Penganggur Oleh Dinas Tenaga Kerja Kabupaten Sleman, Propinsi D.I. Yogyakarta) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRAK This research was aimed to identify the responsiveness of local government on economic crisis focused on one of localgovernmentprograms in responding them who suffered from PI-IK (job firing) and unemployed caused by economic crisis in Sleman. The mentioned program was field of endeavor expansion an un-employed empowerment (PLKPTP) carried out by the Office of Labor and developing the forms of responses/ improvements in this organisation/ bureaucracy when dealing with crisis in the society. The results of the research indicated dominant influences of the organization/ bureaucracy, structure of bureaucracy/ organization and the control intensity of society in the effon' of Local Government, especially the Office of Labor to respond economic crisis in within the society. Therefore, the high responses of Local Government, in this case the office of Labor, was caused b, the ability of organization, structure of bureaucracy/ organization and the social control intensity when the crisis was going on. In general, the responses of Sleman Local Government on crisis was sentiently high.This was proved from the polity and service priott developed in the beginning and during the crisis., in the form of special development policy/ government action programs, such as Social Rescue Programs UPS) that was national packaged financed byAPBN, and PLKPTPpro,gramsfinanced ly the APBD of Sleman Regenry. There were two bureaucracy responses identified in this research. Firstly, changes in the form of rystem/ service mechanism for clients, that were irrigation betterment and rehabilitation were not developed by contractor anymore, but such prole(' works were transferred to the related LKMD (Village SocialActivies Group) that directly involved its populations. Secondly, changes in the form of policy developed by public bureaucracy that was Social Rescue Progam UPS) financed by APBN and PLKPTP form the Office of Labor that was financed by APBD II or Local government an program for tackling food crisis impacts from the Office of Commerce, and action programs that was institutionally implemented